Landform evolution in the Marine Plain region, Vestfold Hills, East Antarctica - Quilty, PG (2006)
Landforms of Marine Plain in the Vestfold Hills contrast with those of most in the Vestfold Hills. They include consistent land surfaces at 40+ m and 25 m, characteristics controlled by orientation of rock features, and imprints of phases of glaciation, deglaciation and marine and freshwater inundation. The 40+ m surface is widespread in the Vestfold Hills and has been noted previously. The 25 m level was an earlier coastline, is more localized and marked by water rounded boulders; it serves to differentiate clearly between two terrains of different relief and erratic distribution. The Pliocene sedimentary rocks below the 25 m level have been dislocated, probably during an interval of glaciotectonism caused by northward movement of sediments under an ice load due to northern extension of the SÃ¸rsdal Glacier or expansion of the East Antarctic Ice Sheet some time after the mid-Pliocene. Soil development is active. These features are accompanied by the normal aspects of a glaciated landscape such as glacial striations, sand wedges, erratics, and patterned ground. Wind has been important in transporting sand and developing honeycomb weathering on exposed rock faces. Â© Antarctic Science Ltd.